2012
DOI: 10.5539/elt.v5n8p207
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Text Typographical Features on Legibility, Comprehension, and Retrieval of EFL Learners

Abstract: This experimental study investigated the relationship between font type, font size, and line spacing and legibility, as measured by speed of reading, comprehension, and recalling. Instruments for testing legibility and reading comprehension were presented in eight typographical styles in print. The study tested 90 students for legibility and 76 students for comprehension. The subjects were chosen from Urmia Language Center in Urmia, Iran, and they were both girls and boys. Two weeks after the reading comprehen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 17 publications
0
7
0
5
Order By: Relevance
“…A coleta foi realizada em ambiente educacional, ambiente real e comum dos sujeitos da pesquisa. (Soleimani & Mohammadi, 2012 ).…”
Section: Amostragemunclassified
See 1 more Smart Citation
“…A coleta foi realizada em ambiente educacional, ambiente real e comum dos sujeitos da pesquisa. (Soleimani & Mohammadi, 2012 ).…”
Section: Amostragemunclassified
“…Resultado também encontrado nos estudos de Soares (2016) que concluiu que fatores simbólicos e estéticos adicionados ao esqueleto das letras, sem alterar seus padrões de maneira significativa, são irrelevantes para o processo de leitura. Soleimani & Mohammadi ( 2012 ) também não encontraram efeitos relevantes na tarefa de leitura comparando letras diferentes, com e sem serifa. Resultados semelhantes obtiveram Arditi & Cho ( 2005 ) sobre a influência das serifas no processo de leitura.…”
Section: Introductionunclassified
“…Using a Likert scale to measure perceived difficulty, it was found that texts with a higher ratio of function words, verbs, verb phrases, or containing more high-frequency words were seen as easier [17-19]. For actual difficulty, simple surface features such as font and line spacing were shown not to affect remembering [20]; however, using a fill-in-the-blanks test additive and causal connectors were shown to be easier than adversative or sequential connectors [21]. In addition to surface features, analysis can include broader features such as coherence, which is defined as good flow combined with a structured, logical argument [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…There are a few researcher focusing in this area. The most recent research is done by (Soleimani and Mohammadi, 2012). They investigate the effects of font selection on comprehension and information recalling.…”
Section: A Serif Versus San Serifmentioning
confidence: 99%